Preparation of Betulinic Acid Derivatives in Organic Solvents - Issak, Anishah (2004)
Betulinic acid has been identified as a potential natural product in medical field. The objectives of this research were to discover a new method for the modification of betulinic acid’s functional groups (C-3 and C-28 position) and to evaluate its activity against cancer cell. Modification at C-3 position was firstly carried out using acetate anhydride/pyridine with chemical reaction of 79% yield and was successfully modified using enzymatic reaction using Novozyme 435 in 85% yield. The later reaction is a new method for the preparation of 3β-acetoxy-lup20(29)-ene-28-oic acid using enzymatic reaction.